2011
DOI: 10.1016/j.neuroimage.2011.06.091
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral hippocampal dysfunction in schizophrenia

Abstract: The hippocampus has long been known to be important for memory, with the right hippocampus particularly implicated in nonverbal/visuo-spatial memory and left in verbal/narrative or episodic memory. Despite this hypothesized lateralized functional difference, there has not been a single task that has been shown to activate both the right and left hippocampus differentially, dissociating the two, using neuroimaging. The transverse patterning (TP) task is a strong candidate for this purpose, as it has been shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 68 publications
(96 reference statements)
8
49
0
Order By: Relevance
“…Recent work on relational memory encoding and retrieval has shown evidence for impaired DLPFC function associated with impaired relational memory function (98) and autobiographical memory (99) in schizophrenia, though other recent work has also implicated hippocampal function (100).…”
Section: Episodic Memory In Schizophreniamentioning
confidence: 99%
“…Recent work on relational memory encoding and retrieval has shown evidence for impaired DLPFC function associated with impaired relational memory function (98) and autobiographical memory (99) in schizophrenia, though other recent work has also implicated hippocampal function (100).…”
Section: Episodic Memory In Schizophreniamentioning
confidence: 99%
“…Here, training was via auditory and visual signals from the mother hen and the relational comparative was food-location preferences along a linear transitive dimension. Humans also have transitivity lateralised to the right hemisphere, so long as the task is not a fully verbal one and the participant is typically-developing (e.g., does not have schizophrenia - Hanlon et al, 2011).…”
Section: Dual Transitive 26mentioning
confidence: 99%
“…Other FMRI studies have confirmed with stimuli from geometric shapes to faces, that the hippocampus as critical to the relational reasoning required for inferring transitive responses when testing follows extensive training (Dickins & Dickins, 2001;Wendelken & Bunge, 2009). The critical importance of the hippocampus in human transitive reasoning has been further corroberated by MEG studies with humans (Hanlon et al, 2011) and PET studies on human participants (Nagode & Pardo, 2002).…”
Section: Brain Research and A Dual-process Account Of Transitivitymentioning
confidence: 99%
“…(e.g. Alvarado & Bachvallier, 2005;Astur & Constable, 2004;Driscoll et al, 2003;Hanlon et al, 2003Hanlon et al, , 2005Hanlon et al, , 2011Meltzer et al, 2008, Moses, Ostreicher, Rosenbaum & Ryan, 2008Moses et al, 2009;Rickard & Grafman, 1998;Rickard, Verfaellie & Grafman, 2006;Reed & Squire, 1996;Ostreicher, Ryan, Moses & Rosenbaum, 2010;Saksida et al, 2007). The transverse patterning task is structurally analogous to the childhood game "rock-paperscissors" (Rock crushes Scissors, Scissors cut Paper, Paper covers Rock), but uses novel stimuli (A, B, C) that have ambiguous meanings outside the context of their pairings (A beats B, B beats C, C beats A; or A+B-, B+C-, C+A-; Fig.…”
Section: Imaging the Potential For Compensationmentioning
confidence: 99%
“…The work of Hanlon et al (2003Hanlon et al ( , 2005Hanlon et al ( , 2011 demonstrates that in adults with hippocampal dysfunction, recruitment of the hippocampus bilaterally may support performance for a task that typically elicits unilateral activation. However, it is unclear whether this effect may be found in developmental populations, since children show different laterality patterns than adults.…”
Section: Meg Studies Of the Organization Of Memory Developmentmentioning
confidence: 99%